Noradrenergic Action in Prefrontal Cortex in the Late Stage of Memory Consolidation - Tronel, Sophie (Cold Spring Harbor Laboratory Press, 2004)
These experiments investigated the role of the noradrenergic system in the late stage of memory consolidation and in particular its action at β receptors in the prelimbic region (PL) of the prefrontal cortex in the hours after training. Rats were trained in a rapidly acquired, appetitively motivated foraging task based on olfactory discrimination. They were injected with a β adrenergic receptor antagonist into the PL 5 min or 2 h after training and tested 48 h later. Rats injected at 2 h showed amnesia, whereas those injected at 5 min had good retention, equivalent to saline-injected controls. Monitoring extracellular noradrenaline efflux in PL by in vivo microdialysis during the first hours after training revealed a significant increase shortly after training, with a rapid return to baseline, and then another increase around the 2-h posttraining time window. Pseudo-trained rats showed a smaller early efflux and did not show the second wave of efflux at 2 h. These results confirm earlier pharmacological and immunohistochemical studies suggesting a delayed role of noradrenaline in a late phase of long-term memory consolidation and the engagement of the PL during these consolidation processes.